Square Pegs in Round Holes: Evaluating Online Delivery for Course Quality - Krystal L Brue Ph.D.; Dana Hilbert Ed.D.; Stephanie Boss Ed.D.; Mary Dzindolet Ph.D.; Jennifer Dennis Ph.D (Academic Chairpersons Conference Proceedings, 2020)
With the expansion of online education, chairs and deans must formulate new strategies for evaluating online course development and instructional delivery. Four chairs (of Business, Education, Sports & Exercise Science, and Psychology Departments), and their dean, will share quality strategies for defining course criteria, developing quality course design, and delivering valued instruction.
Keywords: Online; Design; Delivery; Instructional Evaluation